2012
DOI: 10.1074/jbc.m112.364117
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Arginylation Branch of N-end Rule Pathway in G-protein-mediated Proliferation and Signaling of Cardiomyocytes

Abstract: Background: ATE1 transfers Arg to protein N termini, generating the degron for the N-end rule pathway. Results: ATE1-deficient cardiomyocytes are impaired in the PLC/PKC-MEK1-ERK axis of G␣ q -mediated cardiac signaling. Conclusion:The arginine branch of the N-end rule pathway controls G-protein signaling in cardiomyocytes in part through hypoxia-sensitive degradation of GAP proteins. Significance: This study provides a cellular mechanism underlying cardiovascular defects observed in ATE1-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Interestingly, infusion of an RGS4 peptide lacking the aminoterminus (RGS4DN) reversed the attenuated M 4 response of reserpine-treated neurons, suggesting that RGS4DN acted as a dominant negative inhibitor of endogenous RGS4. RGS4 knockout mice confirmed these results and imply a role for RGS4 in the control in motor symptoms of PD associated with increased striatal acetylcholine levels (Chen et al, 2012;Guasch et al, 2013;Jaba et al, 2013;Lee et al, 2012b;Mighiu and Heximer, 2012;Ruiz de Azua et al, 2012b;Stratinaki et al, 2013;Wydeven et al, 2014).…”
Section: Rgs4supporting
confidence: 78%
“…Interestingly, infusion of an RGS4 peptide lacking the aminoterminus (RGS4DN) reversed the attenuated M 4 response of reserpine-treated neurons, suggesting that RGS4DN acted as a dominant negative inhibitor of endogenous RGS4. RGS4 knockout mice confirmed these results and imply a role for RGS4 in the control in motor symptoms of PD associated with increased striatal acetylcholine levels (Chen et al, 2012;Guasch et al, 2013;Jaba et al, 2013;Lee et al, 2012b;Mighiu and Heximer, 2012;Ruiz de Azua et al, 2012b;Stratinaki et al, 2013;Wydeven et al, 2014).…”
Section: Rgs4supporting
confidence: 78%
“…The studies have demonstrated that the N-end rule pathway has a strikingly diverse range of developmental and physiological roles, which include the regulation of chromosomal stability [14], spermatogenesis [15], oxygen sensing [16, 19], cardiovascular development [18], muscle wasting [2023], proteotoxic protein clearance [25], hypertension [26], autophagy [27], neural tube formation [50], bacterial/viral virulence [52, 53], apoptosis [54], and mitophagy [55]. Mutational inactivation of both copies of the UBR1 gene causes Johanson-Blizzard syndrome (JBS), which involves exocrine pancreatic insufficiency and inflammation, physical malformations, and frequent mental retardation [56].…”
Section: Physiological Implications Of the Mammalian N-end Rule Pathwaymentioning
confidence: 99%
“…Primary MEFs were isolated from mouse embryos approximately on embryonic day (E) 13.5: before the embryonic death from USP14 inactivation [22, 23]. Briefly, embryonic bodies at E13.5 were minced in the presence of trypsin after removal of the head, liver, internal blood clot, and guts.…”
Section: Methodsmentioning
confidence: 99%